Cryptic Triploids and Leaky Premating Isolation in an Odontophrynus Hybrid Zone - Martino, Adolfo Ludovico (2022)
The diploid Odontophrynus cordobae and its autopolyploid counterpart O. americanus (4n) co-occur in a small-sized contact zone in Central Argentina, together with numerous specimens of a cryptic triploid taxon. Additionally, we monitor another five localities inhabited by taxa of this species complex within a radius of 76 km north and south of the contact zone to look for possible co-occurrence of taxa. In this study, we analyze the reproductive interactions in this breeding assemblage covering three levels of ploidy. We focus on the advertisement call structure as a powerful mechanism of premating isolation and on the mating preferences of males and females in the natural habitat. Advertisement calls of triploids were indistinguishable from those of tetraploids, and both differed significantly in pulse rate from diploids. Analyses of 21 amplexi demonstrated that heterospecific matings dominated breeding: one between a diploid female and tetraploid male, and ten between triploids and tetraploids. At three localities with syntopic diploids and tetraploids, premating isolation was almost perfect, preventing the formation of triploids. Therefore, we question the putative origin of triploids from hybridization and discuss alternatives. This unique system, including three bisexual taxa of distinct ploidy, which interact reproductively, remains to be investigated in more detail to fully understand the mechanism stabilizing its persistence.